Technology Adoption in Small-Medium Enterprises based on Technology Acceptance Model: A Critical Review - Adisthy Shabrina Nurqamarani; Eddy Sogiarto; Nurlaeli Nurlaeli (Journal of Information Systems Engineering and Business Intelligence, 2021)
Background: Technology acceptance model (TAM) has been extensively used to analyse user acceptance of technologies adopted by enterprises at different levels. Moreover, the technology adoption has drawn attention among practitioners and academic communities alike, leading to the development of approaches to understand the concept. However, there is a degree of inconsistency found in previous studies on different types of TAM models used in explaining user acceptance of technologies among small-medium enterprises (SMEs).Objective: This critical literature review aims to synthesise the technology adoption scholarly studies using TAM. It is expected to aid the identification of the most relevant factors influencing SMEs in adopting technology. Additionally, analysing the variations of TAM developed in previous studies could provide suggested variables specific to the type of technology industry.Methods: An integrated approach was used, and this involves a review of articles on the adoption of technologies in SMEs from 2011 to 2021, retrieved from popular databases using a mixture of keywords such as technology acceptance model (TAM), technology adoption, and technology adoption in SMEs.Results: An overview of TAM studies on user acceptance of technology in this review covers a wide range of research areas from financial technology to human resource management-related technology. Perceived usefulness and perceived ease of use were discovered to be the most common factors in TAM from the 21 articles reviewed. Meanwhile, some other variables were observed such as context, type of technology and level of user experience.Conclusion: The review highlights key trends in previous studies on IT adoption in SMEs, which assist researchers and developers in understanding the most relevant factors and suitable TAM models in determining user acceptance in a particular field. Keywords: Technology Acceptance Model, Technology Adoption, Small-medium Enterprises, Critical Review